PENGARUH PERBANDINGAN KONSENTRASI TBP : D2EHPA DAN KONSENTRASI PENGEMBAN DALAM FASAORGANIK PADA EKSTRAKSI PERAK DARI LIMBAH FOTO ROENTGEN - Andika Putri, Novita Rusmayanti; Kurniasih, Yeti; Ahmadi, Ahmadi (Hydrogen: Jurnal Kependidikan Kimia, 2016)
Photo roentgen used for examination of internal organs can produce wastes that are harmful to health and the environment because they containing silver metal ion(Ag+) inform of silver thiosulfate complex ([Ag(S2O3)2]-3). Therefore it was necessary for the separation of Ag metal so that the metal does not pollute the environment and can be used economically. One way to separate the metal Ag is by solvent extraction techniques. This study aimed to determine the effect of concentration ratio of TBP:D2EHPA and carrier compound concentration in the organic phase of the percent extraction of silver metal then applied to the sample photo roentgen waste. Extraction of the metals Ag done by varying the ratio of the combined carrier concentration of TBP and D2EHPA in kerosene by concentration ratio was 0: 1; 0.25: 0.75; 0.5: 0.5; 0.75: 0.25 and 1: 0 M as well as by varying the carrier concentration in the organic phase ranging from 0 M; 0.5 M; 1 M and 1.5 M. Measuring the concentration of metal ions Ag+in water phase before and after extraction was determined by atomic absorptionspectrophotometer (AAS) at a wavelength of 328,22 nm then calculated percent extraction. Based on the research that obtained the highest percent extraction on single used carrier compounds and compound concentration carrier D2EHPA in optimum water was 0.5 M with 58.22% percent extraction. Applications optimum conditions to the extraction of silver metal obtained from photo roentgenwaste percent extraction was 10.27%.